Smart Home Security Analysis Using Microcontroller - S, Arjun; V, GopiKrishna; B, Gowtham; B, Siddharthan; Manikandan, V. (IRO Journal on Sustainable Wireless Systems, 2023)
To prevent data theft, unauthorized access, and network misuse, data modification network security plays a major role in it. Another important role is preventing DOS (Denial Of Service) attacks and making sure of uninterrupted service for legal network users. Network Security also has some defense protocols to protect the data from internal and external attacks. The proposed work is based on creating a safe and secure network by creating a double authentication i.e., by using mail and SMS. Double authentication can also be used in banks as many thefts are being done in a single authentication, if double authentication is implemented through SMS and mail it provides additional security for transactions that are done online. This research is implemented with the help of servers and a microcontroller to develop an application that is essential in a smart home design.
Keywords: Microcontroller; Cybersecurity; smart home; authentication